(untitled) - MacBlain, Sean (London, 2014)
Understanding how children learn is a vital part of working with children. Every child is unique and understanding differences in learning helps all to benefit. Going beyond simply understanding the work of key theorists and the various theories of learning, this text helps you recognize what learning actually looks like and how it is best facilitated in any setting. Looking at key topics such as brain development, technology in childhood and barriers to learning, you gain a deeper understanding of what learning really is. Each chapter includes a range of features to support your learning.
Keywords: Learning, Psychology of,Học tập, Tâm lý học